Art of success: learning through great conquerors from Julius Caesar to Genghis Khan - Kim Hoo (Quezon City, 2007)
In this book, we find positive techniques for success that turn the minus to plus in the evil conduct of conquerors and introduce techniques to people living in today's modern sociery.
Keywords: Conquerors; Success; Success-Psychological Aspects